2020
DOI: 10.1051/bioconf/20201700089
|View full text |Cite
|
Sign up to set email alerts
|

Sanding of drained peatlands

Abstract: The results of many years of original research based on soil-ecological monitoring showed the development of degradation processes of previously drained peat soils of the Ryazan Meshchera. Structural amelioration (sanding) of peat soils had some positive effect. The aim of the research was to study the properties of the dried peat soil at reclamation site Tinki-II in the settlement of Polkovo, Ryazan District of Ryazan Region, as a result of sanding. The most common type of German mixed-layer sanding was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The response of labile organic matter to drainage and siltation supported our hypothesis that siltation of drained peatlands hampers the mineralization of the remaining peat layers. It was notable that siltation did not stop the mineralization but to some extent retarded the negative changes and loss of organic C. The results of our study are in line with the previous findings of the positive effect of peatland sanding [32]-covering peatlands with a layer of sand to enable agricultural use of peatlands.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The response of labile organic matter to drainage and siltation supported our hypothesis that siltation of drained peatlands hampers the mineralization of the remaining peat layers. It was notable that siltation did not stop the mineralization but to some extent retarded the negative changes and loss of organic C. The results of our study are in line with the previous findings of the positive effect of peatland sanding [32]-covering peatlands with a layer of sand to enable agricultural use of peatlands.…”
Section: Discussionsupporting
confidence: 90%
“…Siltation occurring on the peatlands located near the slopes may have a similar effect. Zakharova et al [32] reported that the sanding of peat soils had some positive effect, i.e., improved soil physical properties. From an environmental point of view, Zaidel'man et al [33] reported that sand application increases the loss of peat organic matter via CO 2 emission from the soil surface to the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that point defects of the structure are formed in quartz crystals under the action of neutrons, local centers are transformed and structural phase transformations are observed [1,2]. The study of various physicochemical properties of neutron-irradiated crystals shows that up to doses of 10 17 n/cm 2 , mainly the manifestation of pre-radiation defects, impurity color centers, transformation of local centers and radiation-induced point defects of the structure is observed [3].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are homogenized with surface soil horizons or were leached into the deeper horizons during cultivation on peatlands (Kalisz et al, 2021). Former studies reported that the soil amendment type significantly affected soil physical properties, soil nutrients, and the size of soil seed banks (Zakharova et al, 2020;Kalisz et al, 2021;Smolczynski et al, 2021). However, poor information is available on whether topsoil removal can help in restoring the target species, such as Carex species, and how soil amendment types affect vegetation restoration in farmed peatlands during restoration.…”
Section: Introductionmentioning
confidence: 99%